Managing diversity in Malaysia: readiness of non-Malay youths to join the Malaysian Armed Forces - Dahalan, Dzuhailmi; Ismail, Ismi Arif; D’Silva, Jeffrey Lawrence; Abu Samah, Asnarulkhadi; Kamarudin, Nurul Akhtar (Human Resource Management Academic Research Society, 2022)
This article examines the readiness level of non-Malay youths in Malaysia in joining the Malaysian Armed Forces (ATM) with regard to several factors, namely attitude, subjective norms and perceived behaviour control. The findings presented are based on a quantitative study involving a total of 1033 respondents who are currently pursuing formal education at selected secondary schools in Malaysia. In general, the study discovered that attitude and subjective norms of respondents towards the ATM are at a moderate level while their perceived behavioural control towards joining the ATM in the future is low. There is a significant difference on respondents’ attitudes, subjective norms and perceived behaviour control towards the ATM based on where they live permanently. Respondents residing in rural areas were seen to have a slightly higher readiness than respondents residing in urban areas in joining the ATM in the future based on the attitudes, subjective norms and perceptions of behaviour control factors among them. To summarise, the findings of the study verify that the issue on the involvement of the non-Malay in the ATM, in particular among the youths, is indeed a national issue that has previously been raised. In fact, the findings of the study indicate that this issue will remain relevant as a subject of interest that can be studied further from time to time. Therefore, the current study suggests that efforts to foster positive attitudes and increase subjective norms and perceived behavioural control for a career in the ATM should be carried out continuously in a more structured and systematic way to increase the readiness of non-Malay youths in Malaysia to join the ATM. This is important in order to celebrate ethnic diversity in the nation defense sector as well as to foster the spirit of patriotism among non-Malay youths in Malaysia.